FRI0148 SEROLOGICAL PROFILES IN PRIMARY SJÖGREN SYNDROME, SJOGRENSER PROJECT. (2nd June 2020) - López-González, R.; Sánchez-Piedra, C.; Fernandez Castro, M.; Andreu, J. L.; Olive, A.; Martinez Taboada, V.; Rosas, J.
Abstract : Objectives: Primary Sjögren´s Syndrome (pSS) is characterized by hyperactivity of the B cell, with the consequent production of autoantibodies. The presence of anti-Ro and anti-La has been associated with extraglandular manifestations and lymphoma development. The aim of this study is to evaluate the frequency of different serological profiles in patients of SJOGRENSER registry and to assess whether the combination of antibodies and serological markers are associated with the development of systemic disease and the systemic illness and/or the development of systemic disease and complications. Methods: SJOGRENSER is a transversal multicenter study with pSS patients (patients who meet 2002 pSS classification criteria); it is collected demographic, clinical, serological data and the activity index: ESSDAI and ESSPRI. It was established three serological profiles: 1. ANA/Ro+ with La/RF-; 2. ANA/Ro/La+ with RF-; 3. ANA/Ro/La/RF+. A descriptive analysis was done, with means and standard deviations, frequencies and proportions. Student t for quantitative variables and Chi2 for qualitative ones were performed to evaluate differences between groups, it was considered a p <0.05 as significant. The association was analyzed by multinominal analysis. Results: Four hundred and thirty-seven patients were included, the most frequent serological patterns observed were: ANA/Ro/La/RF+ 221 patients (50.5%), ANA/Ro/La+ 61 patients (13.9%) and ANA/Ro+ 60 patients(13.7%). There were only two patients with ANA/La +. The ESSDAI score was significantly associated with the profile ANA/Ro/La/RF+ (6 vs 4, p=0.007) and the group with the ANA/Ro/La+ profile reached an ESSDAI<5 (79%, p=0.043) (Table 1 ). In contrast to the ESSPRI index was lower significantly associated with the profile ANA/Ro/La/RF+ and higher in the ANA/Ro+ (5 vs 6.1, p=0.007). The presence of antiLa and/or RF to the profile ANA/Ro+ rises the percentage of patients with constitutional syndrome, glandular, kidney and hematological affectation with statistically significant differences. The percentage of patients with articular involvement it was similar in the profiles ANA/Ro+ and ANA/Ro/La/RF +. The multinomial analysis showed that the profile ANA/Ro/La/RF+ was associated with higher ESSDAI values (OR=1.09 (1.01-1.17)). The hematological involvement was associated with the profiles ANA/Ro/La/FR+ (OR= 2.76 (1.46-5.22)). Higher scoring of ESSPRI was associated with the profile ANA/Ro+ (OR=0.79 (0.69-0.91)). Conclusion: The most frequent serological profile was ANA/Ro/La/RF+ and it was associated with higher ESSDAI score. The presence of antiLa and/or RF with an ANA/Ro+ increased the presence of systemic involvement. The ANA/Ro+ profile was associated with a higher level of ESSPRI. Disclosure of Interests: None declared